2019
DOI: 10.1261/rna.070706.119
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific m6A demethylation in RNA by FTO fused to RCas9

Abstract: N 6-methyladenosine (m 6 A) is the most common internal modification in eukaryotic mRNA and associated with numerous cellular processes in health and disease. Up-and down-regulation of its "writer" or "eraser" proteins alter the global m 6 A level; however, modifying distinct m 6 A sites has remained elusive. We genetically fused the dioxygenase FTO responsible for m 6 A demethylation to RCas9 as an RNA-targeting module. The resulting RCas9-FTO retained demethylation activity and bound to RNA in a sequence-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 113 publications
0
26
0
1
Order By: Relevance
“…It has been shown that removal of the m6A modification in lncRNA MALAT1 at A2577 resulted in structural change and altered the interaction with the RNA binding protein hnRNPC [87]. A similar dCas9-FTO system has also been reported by another group [88]. In another study, Rauch et al made use of the newly identified RNA-guide RNA targeting CRISPR/ Cas13 system to interrogate the functional consequence of the binding of different m6A "reader" proteins to the targeted RNA.…”
Section: Future Prospectsmentioning
confidence: 79%
“…It has been shown that removal of the m6A modification in lncRNA MALAT1 at A2577 resulted in structural change and altered the interaction with the RNA binding protein hnRNPC [87]. A similar dCas9-FTO system has also been reported by another group [88]. In another study, Rauch et al made use of the newly identified RNA-guide RNA targeting CRISPR/ Cas13 system to interrogate the functional consequence of the binding of different m6A "reader" proteins to the targeted RNA.…”
Section: Future Prospectsmentioning
confidence: 79%
“…So we still lack a flexible approach to remove m 6 A with spatial and temporal specificity. Recently, some effective RNA m 6 A editing methods were reported by CRISPR-dCas9 conjugates and other programmable RNA binding proteins, [29][30][31] but with sufficient space for improvement.…”
Section: Resultsmentioning
confidence: 99%
“…[29] Rcas9 was also chosen as the RNA-targeting protein to realize sequence-specific m 6 A demethylation. [30] However, these technologies still need to be improved for two reasons. First, additional PAMer DNA with multiple 2′-OMe modifications should be co-transfected via two kinds of transfection reagents that increase the cost and complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit SCARLET with low-throughput and fancy features, the feasibility and accuracy allow SCARLET to be a frequently-used strategy for examining the accuracy of high-throughput detection of m 6 A modification. And SCARLET can also be allowed to screen other types of epigenetic modifications in RNA, such as m 5 C and Ψ modifications [25]. Golovina et al reported a strategy based on high-resolution melting analysis for monitoring m 6 A sites in a specific RNA position [26].…”
Section: Detection Of M 6 a Methylationmentioning
confidence: 99%